Dangerous Motherhood - Marland, H. author. aut Link
XII, 303 p.
Keywords: Dangerous Motherhood is the first study of the close and complex relationship between mental disorder and childbirth. Exploring the relationship between women, their families and their doctors reveals how explanations for the onset of puerperal insanity were drawn from a broad set of moral, social and environmental frameworks, rather than being bound to ideas that women as a whole were likely to be vulnerable to mental illness. The horror of this devastating disorder which upturned the household, turned gentle mothers into disruptive and dangerous mad women, was magnified by it occurring at a time when it was anticipated that women would be most happy in the fulfillment of their role as mothers.